Conceptions about mathematics teaching in teachers of primary public schools - Moreano, Giovanna (2008)
This paper is part of a qualitative research study that took place in five public schools of Lima between 2005 and 2007. The goal was to identify teachers’ conceptions about teaching and learning in order to understand their pedagogic practice. The sample included 9 sixth grade teachers of primary schools. Results show that traditional pedagogic conceptions are strongly rooted and this is reflected in the pedagogic practice of all teachers. Mathematics teaching is characterized by the following of rules and procedures, the routine practice of exercises, the use of key words and the lack of a significant context for learning.